Pendampingan Implementasi Nilai Etika pada Santri di Taman Pendidikan Quran Al-Hayatul Islamiyah Kota Malang - Fitriyah, Amirotul; Inayah, Mashunatul; yafa’atul Chusnia, Trysia S; Said, Akhmad (STAI Ma'had Aly Al-Hikam Malang, 2024)
Abstract Character education has a crucial role in forming individuals who are not only academically intelligent but also have strong ethical sustainability. Devotion is carried out in applying ethical values ​​to students Taman Pendidikan Al-Quran (TPQ) Al Hayatul Islamiah as an effort to create a generation with noble morals. Through a holistic approach, TPQ integrates Islamic religious teachings into the curriculum, ensuring that students not only become hafidz of the Koran but also individuals who are committed to ethical and moral values ​​in everyday life. By involving teachers, administrators, and parents, TPQ Al Hayatul Islamiah creates a deep and engaging educational environment, where Islamic values ​​are embedded in every aspect of life. This article explains the concrete steps taken by TPQ to teach and practice ethical values, such as honesty, responsibility, and compassion, so that students become not only someone capable, but also individuals who are empowered, have high morals and are ready to face global challenges with confidence and integrity. Keywords: Implementation of ethical values, Moral, Santri. Abstrak Pendidikan karakter mempunyai peranan yang sangat penting dalam membentuk individu yang tidak hanya cerdas secara akademis namun juga memiliki ketahanan etika yang kuat. Pengabdian yang dilakukan dalam penerapan nilai etika dan moral pada santri Taman Pendidikan Al-Quran (TPQ) Al Hayatul Islamiah sebagai upaya mewujudkan generasi berakhlak mulia. Melalui pendekatan holistik, TPQ mengintegrasikan ajaran agama Islam ke dalam kurikulum, memastikan peserta didik tidak hanya menjadi hafidz Al-Quran tetapi juga individu yang berkomitmen terhadap nilai-nilai etika dan moral dalam kehidupan sehari-hari. Dengan melibatkan guru, pengurus, dan orang tua, TPQ Al Hayatul Islamiah menciptakan lingkungan pendidikan yang mendalam dan menarik, dimana nilai-nilai Islam tertanam dalam setiap aspek kehidupan. Artikel ini menjelaskan langkah konkrit yang dilakukan TPQ dalam mengajarkan dan mengamalkan nilai-nilai etika, seperti kejujuran, tanggung jawab, dan kasih sayang, agar peserta didik tidak hanya menjadi seseorang yang cakap, namun juga menjadi individu yang berdaya, berakhlak mulia, dan siap menghadapi tantangan global dengan percaya diri dan integritas. Kata Kunci: Implementasi Nilai Etika, Moral, Santri.